Long-term follow-up of patients with non-Hodgkin lymphoma following myeloablative therapy and autologous transplantation of CD34+-selected peripheral blood progenitor cells - Witzens-Harig, Mathias; Heilmann, Conny Yvonne Xenia; Hensel, Manfred; Kornacker, Martin; Benner, Axel; Haas, Rainer; Frühauf, Stefan; Ho, Anthony Dick (Stem cells, 2007)
Graft engineering by CD34+ selection of peripheral blood progenitor cells (PBPC) has been used in non-Hodgkin lymphoma (NHL) with the aim to reduce relapse related to tumor cells within the graft. From September 1995 to January 2000, 39 patients with newly diagnosed (n = 31) or relapsed (n = 8) NHL were treated in our institution with myeloablative therapy followed by CD34+ selected autologous PBPC transplantation. Thirty-one patients were diagnosed with follicular lymphoma, and eight patients with mantle-cell lymphoma. All patients had advanced disease (26% of patients stage III and 74% stage IV, Ann Arbor classification). Induction therapy resulted in a complete remission in 17 patients and a partial remission in 22 patients. PBPC were mobilized after cytotoxic chemotherapy with granulocyte colony-stimulating factor support. CD34+ selection was performed using immunomagnetic beads (Baxter Isolex 300SA or 300i Magnetic Cell Separation System). Most patients (85%) received total body irradiation and high-dose cyclophosphamide as myeloablative regimen. Twelve patients also received rituximab 375 mg/m2 before radiation and before the start of the cyclophosphamide treatment. The mean CD34+ cell number for transplantation was 6.5 × 106 CD34+ cells/kg of body weight. Platelet recovery (>20,000/μl median on day 13) and leukocyte recovery (>1,000/μl median on day 12) were within expected range. The estimated median follow-up was 47 months. The probabilities of freedom from progression, overall survival, and event-free survival 4 years after transplantation were 96%, 90%, and 87%, respectively, for patients with follicular lymphoma and 42%, 63%, and 33%, respectively, for patients with mantle-cell lymphoma. Risk factors for relapse were age and extranodal manifestation of disease. The rate of lethal infections in the 12-month follow-up period was 8%. We conclude that CD34+ selection of autologous transplants following myeloablative therapy is feasible and results in long-term remission in the majority of patients, but the procedure is probably related to a higher rate of lethal infections.
Das Pluszeichen im Titel ist hochgestellt
Frontdoor: First published: 02 January 2009
Gesehen am 05.11.2021